Impact of seasonality and forest stand age on ion deposition in rehabilitated forests - Mohamad Hilmi, Ibrahim; Salwana, Jaafar; Naoyuki, Yamashita; Hiroyuki, Sase (John Wiley & Sons, Inc, 2024)
This study examines the critical interaction between seasonal precipitation variability and forest maturity in determining ion deposition patterns in rehabilitated forest ecosystems. This research was conducted in rehabilitated forest sites in Bintulu, Sarawak, Malaysia that had ecologically similar plant distribution, species, and age in each planting area. This facilitated the standardization of rainfall deposition in the different study plots which streamlined the study of these specific facets of ecosystem dynamics. The goal is to understand how seasonal changes and the age of the forest influence the chemical composition of the flux that relates to the movement and deposition of nutrients through the forest ecosystem. This flux is a key factor in the health of the forest ecosystem and nutrient cycling. Using ion exchange resin (IER) samplers, we accurately measured and compared the deposition of different ions (Ca2+, Na+, Fe2+, Cu2+, NO3 − , NH4 + and SO4 2−) across different seasons and forest ages. The deposition of Ca2+ and NH₄+ was significantly lower in the low-precipitation season than in the high-precipitation season in all forest stands, regardless of the year they were established (1996, 1999, 2002, 2005, and 2009). In contrast, ions such as Na+, Fe2+, Cu2+, NO3 − and SO4 2− showed no clear seasonal fluctuations. In addition, the study shows that through-fall in forest stands from 2002, 2005 and 2009 had higher concentrations of Ca2+ in both seasons than in 1996 and 1999. Interestingly, forest stands from 2009 and 2002 had elevated levels of Na+ and SO₄2− in seasons with low precipitation, while stands from 1996 had higher levels in seasons with high precipitation. Our results emphasize the crucial role of precipitation amount and canopy age in determining ion deposition in forest ecosystems. By demonstrating the significant influence of precipitation seasonality and forest maturity on the chemical composition of throughfall, this study contributes to a deeper understanding of nutrient dynamics in developing forest landscapes and provides valuable insights for